2015
DOI: 10.1111/jnc.13132
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle exocytosis and increased cytosolic calcium are both necessary but not sufficient for activity‐dependent bulk endocytosis

Abstract: Activity-dependent bulk endocytosis (ADBE) is the dominant synaptic vesicle (SV) endocytosis mode in central nerve terminals during intense neuronal activity. By definition this mode is triggered by neuronal activity; however, key questions regarding its mechanism of activation remain unaddressed. To determine the basic requirements for ADBE triggering in central nerve terminals, we decoupled SV fusion events from activity-dependent calcium influx using either clostridial neurotoxins or buffering of intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
4
25
0
Order By: Relevance
“…In contrast, Alix ko neurons failed to endocytose dextran ( Figure 6A, B) even though bicuculline/4AP stimulation increased calcium entry (Supplementary figure 2A) and neuronal activity (Supplementary figure 4C, D) in both Alix ko and wt neurons. As already shown (Morton et al, 2015), neurons also failed to endocytose dextran when treated with calcium chelators BAPTA and EGTA (Supplementary figure 4E), both of which blocked Alix recruitment to presynaptic boutons (Supplementary figure 3). Finally, rescue experiments showed that the impairment in ADBE observed in Alix ko cells is due solely to the absence of Alix, since restoring Alix expression fully restored the capacity of Alix ko cells to endocytose 10 kDa dextran (Figure 6 C, D).…”
Section: Alix Is Required For Adbesupporting
confidence: 66%
“…In contrast, Alix ko neurons failed to endocytose dextran ( Figure 6A, B) even though bicuculline/4AP stimulation increased calcium entry (Supplementary figure 2A) and neuronal activity (Supplementary figure 4C, D) in both Alix ko and wt neurons. As already shown (Morton et al, 2015), neurons also failed to endocytose dextran when treated with calcium chelators BAPTA and EGTA (Supplementary figure 4E), both of which blocked Alix recruitment to presynaptic boutons (Supplementary figure 3). Finally, rescue experiments showed that the impairment in ADBE observed in Alix ko cells is due solely to the absence of Alix, since restoring Alix expression fully restored the capacity of Alix ko cells to endocytose 10 kDa dextran (Figure 6 C, D).…”
Section: Alix Is Required For Adbesupporting
confidence: 66%
“…One potential mechanism for the increased prevalence of ADBE is an increase in the number of SVs fusing, providing an increased endocytic load ( 66 ). To determine this, we monitored SV exocytosis using synaptophysin-pHluorin (syp-pH) ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in response to intense stimulation, ADBE takes up large quantities of fused SVs from the plasma membrane to form bulk cisternae. It has been shown that both SV exocytosis and intracellular Ca 2+ elevation are essential for ADBE to proceed around the periactive zones [ 7 , 18 , 26 ]. This raises the possibility that Fwe may play a role in ADBE.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, following high K + stimulation, the accumulation of early endocytic intermediates was observed around the periactive zone in fwe mutant boutons ( Fig 2D–2D1 and 2I , yellow arrows) when compared to wild-type controls and 50% Fwe-rescued larvae ( Fig 2B–2B1, 2F–2F1 and 2I ). Since optimal SV exocytosis is shown as a prerequisite for triggering ADBE [ 7 , 26 ], we therefore estimated the total SV area per bouton area under the resting condition. No difference between controls and fwe mutants was found ( Fig 2J ), showing that the ADBE defect associated with fwe mutants is not due to insufficient supply of exocytic SV membrane upon stimulation.…”
Section: Resultsmentioning
confidence: 99%